UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN CURAH PENDAPAT (BRAINSTORMING) PADA MATA PELAJARAN PEDIDIKAN KEWARGANEGARAAN DI SMA NEGERI 1 TOMA TAHUN PEMBELAJARAN 2022/2023 - Darwin Gaurifa (Universitas Nias Raya, 2023)
The purpose of this research is to find out the increase in student learning outcomes through the application of the Brainstorming Learning Model in the Citizenship Education Subject in Class X SMA Negeri 1 Toma in the 2022/2023 Academic Year. This research is a quantitative research carried out according to the Classroom Action Research (PTK) model, namely planning, action, observation, and reflection. Based on the results of the implementation of learning and research discussion it was concluded that the results of the percentage of students' learning completeness in cycle I only reached 61.76% with an average student learning outcome of 68.88 in the sufficient category. For the results of Observation of Teacher Respondents in Cycle I was 75% in the good category, while the results of observations of learning activities in cycle I were 53.33 in the poor category. After reflecting on cycle I, cycle II was carried out, that is, during the implementation of learning took place in cycle II, the percentage of student learning completeness was 100% with an average student learning outcome of 92.88 in the very good category. For the results of observing the learning activities of the teacher respondents in cycle II was 92.85 in the Very Good category while the results of observing the implementation of learning activities in cycle II were 94.44% in the Very Good category. Based on the research findings, the researcher can conclude that using the Brainstorming Learning Model can improve student learning outcomes, and can also improve the quality of learning. From the results of the research conducted, the researchers provide suggestions that it is better if the teacher in carrying out learning, especially in civics education subjects, applies the brainstorming learning model so that learning becomes more optimal and learning outcomes can be more improved.